2020
DOI: 10.1080/1331677x.2020.1734855
|View full text |Cite
|
Sign up to set email alerts
|

Income inequality, innovation and carbon emission: Perspectives on sustainable growth

Abstract: The present study aims to investigate the impact of income inequality and economic growth on carbon dioxide (CO2) emission through the moderating role of innovation in China at national and regional levels. To test the hypothesised relationships, this study took the data from 1995 to 2015 and employed panel estimation. Findings of the whole analysis show that income inequality and economic growth influence CO2 emission in China. Moreover, technological innovation moderates the proposed link. However, the findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 62 publications
3
21
0
Order By: Relevance
“…This result is consistent with the previous ndings for India (Dar & Asif, 2017); Pakistan (Chandia, Gul, Aziz, Sarwar, & Zul qar, 2018;Ur Rahman et al, 2019); China (Manzoor Mushtaq et al, 2020;Wei, 2020;Zhou et al, 2018); the US (Alola & Alola, 2019); Liberia (Moutinho et al, 2020); Qatar (Mrabet, AlSamara, & Hezam Jarallah, 2017); selected 72 countries (Inekwe, Maharaj, & Bhattacharya, 2019); developing countries (Wawrzyniak & Doryń, 2020); NAFTA and BRIC (Rahman et al, 2019); SEE countries (Obradović & Lojanica, 2017); and Asian economies (Qingquan et al, 2020). (Kasman & Duman, 2015).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…This result is consistent with the previous ndings for India (Dar & Asif, 2017); Pakistan (Chandia, Gul, Aziz, Sarwar, & Zul qar, 2018;Ur Rahman et al, 2019); China (Manzoor Mushtaq et al, 2020;Wei, 2020;Zhou et al, 2018); the US (Alola & Alola, 2019); Liberia (Moutinho et al, 2020); Qatar (Mrabet, AlSamara, & Hezam Jarallah, 2017); selected 72 countries (Inekwe, Maharaj, & Bhattacharya, 2019); developing countries (Wawrzyniak & Doryń, 2020); NAFTA and BRIC (Rahman et al, 2019); SEE countries (Obradović & Lojanica, 2017); and Asian economies (Qingquan et al, 2020). (Kasman & Duman, 2015).…”
Section: Resultssupporting
confidence: 92%
“…This relationship is commonly referred to as the EKC hypothesis. Several researchers have validated the EKC hypothesis for different economies, including but not limited to, Iberia (Moutinho, Madaleno, & Bento, 2020); China (Jiang, Yang, & Ma, 2019;Mushtaq, Chen, Din, Ahmad, & Zhang, 2020;Zhou et al, 2018); India (Dar & Asif, 2017); Pakistan (Ur Rahman, Chongbo, & Ahmad, 2019); USA (Alola & Alola, 2019);Brazil (Ben Jebli & Ben Youssef, 2019); emerging economies (Wawrzyniak & Doryń, 2020); NAFTA and BRIC (Rahman, Cai, Khattak, & Hasan, 2019); Ukraine (Melnyk, Kubatko, & Kubatko, 2016); SEE economies (Obradović & Lojanica, 2017); developed and developing economies (Anser et al, 2020);and OECD (Manzoor Ahmad, Khan, Rahman, Khattak, & Khan, 2019).…”
Section: The Relationship Between Income and Co 2 Ementioning
confidence: 99%
“…Likewise, the estimated coefficient of urban population is significant and negative in the first two models and insignificant in the third model. (Mushtaq, Chen, Ud Din, Ahmad, & Zhang, 2020) also found that urban population decrease carbon emission in china.…”
Section: Resultsmentioning
confidence: 88%
“…The empirical estimates ofKasuga & Takaya (2017) reveal a positive and statistically significant impact of inequality (90 th /10 th ) on SO2, NOX, and SPM for Japanese cities in the residential and commercial areas. Based on the provincial panel data of China,Hao et al (2016) emphasize the importance of regional differences in analyzing the link between income inequality and carbon emissions Mushtaq et al (2020). confirm the regional difference in China for the larger time-period by using alternative estimators and emphasizing the moderating role of innovation.…”
mentioning
confidence: 88%